Activated Erk Is an Early Retrograde Signal After Spinal Cord Injury in the Lamprey - Jin, Li-Qing; John, Brittany H.; Hu, Jianli; Selzer, Michael E. (Frontiers in Neuroscience, 2020)
We previously reported that spinal cord transection (TX) in the lamprey causes mRNA to accumulate in the injured tips of large reticulospinal (RS) axons. We sought to determine whether this mRNA accumulation results from phosphorylation and transport of retrograde signals, similar to what has been reported in mammalian peripheral nerve. Extracellular signal-regulated protein kinase (Erk), mediates the neurite outgrowth-promoting effects of many neurotrophic factors. To assess the role of Erk in retrograde signaling of RS axon injury, we used immunoblot and immunohistochemistry to determine the changes in phosphorylated Erk (p-Erk) in the spinal cord after spinal cord TX. Immunostaining for p-Erk increased within axons and local cell bodies, most heavily within the 1-2 mm closest to the TX site, at between 3 hours and 6 hours post-TX. In axons, p-Erk was concentrated in 3-5 µm granules that became less numerous with distance from the TX. The retrograde molecular motor dynein colocalized with p-Erk, but vimentin, which in peripheral nerve was reported to participate with p-Erk as part of a retrograde signal complex, did not colocalize with p-Erk, even though vimentin levels were elevated post-TX. The results suggest that p-Erk, but not vimentin, may function as a retrograde axotomy signal in lamprey central nervous system neurons, and that this signal may induce transcription of mRNA, which is then transported down the axon to its injured tip.